2020
DOI: 10.3390/jcm9072315
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmatic Aldosterone and C-Reactive Protein Levels, and the Severity of Covid-19: The Dyhor-19 Study

Abstract: Background. The new coronavirus SARS-CoV-2, responsible for the Covid-19 pandemic, uses the angiotensin converting enzyme type 2 (ACE2), a physiological inhibitor of the renin angiotensin aldosterone system (RAAS), as a cellular receptor to infect cells. Since the RAAS can induce and modulate pro-inflammatory responses, it could play a key role in the pathophysiology of Covid-19. Thus, we aimed to determine the levels of plasma renin and aldosterone as indicators of RAAS activation in a series of consecutively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 28 publications
3
45
3
1
Order By: Relevance
“…As a result of the viral tropism to the kidneys, acute renal injury was found to be the second most observed COVID-19 complication in the USA (22.2%) [ 77 ] and China (25.2%) [ 67 ]. Thus, there is compelling evidences that patients with acute kidney injury at admission exhibit activation of RAAS, as documented by higher plasmatic renin and aldosterone levels and lower urinary sodium levels in patients with acute kidney injury [ 109 ], as well as the association of plasmatic aldosterone and C-reactive protein levels and COVID-19 severity [ 110 ]. Since hypokalaemia was found to be prevalent in patients with COVID-19 pneumonia (~ 30%) and is an indicator of RAAS activity, it was suggested that hypokalaemia could be used as a surrogate marker of COVID-19 progression and an independent risk factor for invasive mechanical ventilation requirement [ 111 ].…”
Section: Comorbidities and Ace/ace2 Balance Disruptionmentioning
confidence: 99%
“…As a result of the viral tropism to the kidneys, acute renal injury was found to be the second most observed COVID-19 complication in the USA (22.2%) [ 77 ] and China (25.2%) [ 67 ]. Thus, there is compelling evidences that patients with acute kidney injury at admission exhibit activation of RAAS, as documented by higher plasmatic renin and aldosterone levels and lower urinary sodium levels in patients with acute kidney injury [ 109 ], as well as the association of plasmatic aldosterone and C-reactive protein levels and COVID-19 severity [ 110 ]. Since hypokalaemia was found to be prevalent in patients with COVID-19 pneumonia (~ 30%) and is an indicator of RAAS activity, it was suggested that hypokalaemia could be used as a surrogate marker of COVID-19 progression and an independent risk factor for invasive mechanical ventilation requirement [ 111 ].…”
Section: Comorbidities and Ace/ace2 Balance Disruptionmentioning
confidence: 99%
“…Early data on kidney function have shown that patients who are admitted to the hospital for COVID-19 have an increase in protein in the urine (proteinuria) and blood in the urine (hematuria) ( 14 ). Patients with a severe clinical course for COVID-19 show higher circulating renin, ANG II, and aldosterone compared with those with mild COVID-19 clinical complications ( 58 ). Moreover, acute kidney injury (AKI) occurs in nearly 36.6% of SARS-CoV-2-infected patients ( 59 ).…”
Section: Heart and Kidneysmentioning
confidence: 99%
“…In addition, potassium canrenoate (the active metabolite of spironolactone) results in concentration (0.1-10 μM)-dependent reductions of the binding of the SARS-CoV-2 spike protein to the ACE2 receptor ( Carino et al, 2020 ). Increased plasma aldosterone levels associated with disease severity in COVID-19 patients ( Villard et al, 2020 ) suggest that MRBs may have beneficial effects in COVID-19. A recent study concluded that canrenone decreased all-cause mortality and improved the clinical outcome in a small cohort of 30 COVID-19 patients with diseases ranging from moderate to severe (M. Vicenzi et al, 2020 ).…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 99%